Production of Hydrogen through Methane Steam Reforming in a Fixed Bed Reactor Using MATLAB Simulation (University of Khartoum Engineering Journal, 2022)
A novel simulation approach was adopted in this paper based on the reactants conversion rather than the number of moles of components. The reaction of steam reforming of methane in a fixed bed reactor with the presence of nickel based catalyst was theoretically studied and analyzed. A mathematical model was developed to simulate the process using MATLAB to see how the changes in the operating parameters can affect the rate of production of hydrogen and tube skin temperature. The reformer operating conditions were optimized.